2012
DOI: 10.1177/0885066612453025
|View full text |Cite
|
Sign up to set email alerts
|

The GENESIS Project (GENeralized Early Sepsis Intervention Strategies)

Abstract: Patients with severe sepsis and septic shock receiving the RB in community and tertiary hospitals experience similar and significant reductions in mortality and hospital length of stay. These findings remained consistent when examined in both before-and-after and concurrent analyses. Early sepsis intervention strategies are associated with 1 life being saved for every 7 treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 43 publications
2
22
1
Order By: Relevance
“…Also, a higher concentration of biomarkers has been considered to have prognostic significance, as indicative of greater activation of the inflammatory and vasoactive systems [22,23,39]. However, implementing those measures indicated in the Surviving Sepsis Campaign [29], especially early surgical treatment if indicated, immediate antibiotic therapy, adequate and timely volume restitution, and initiating catecholamine treatment, the clinical course of patients could be better and, at least in part, independent of baseline characteristics [57,58]. In fact, the unique factor associated with survival was the significant decrease in the serum concentration of PCT.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a higher concentration of biomarkers has been considered to have prognostic significance, as indicative of greater activation of the inflammatory and vasoactive systems [22,23,39]. However, implementing those measures indicated in the Surviving Sepsis Campaign [29], especially early surgical treatment if indicated, immediate antibiotic therapy, adequate and timely volume restitution, and initiating catecholamine treatment, the clinical course of patients could be better and, at least in part, independent of baseline characteristics [57,58]. In fact, the unique factor associated with survival was the significant decrease in the serum concentration of PCT.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, a multi-center study of 2,424 septic shock patients by Cannonet al found that 37.6% patients had alactatemia. 13 The cause of alactatemia remains unclear. In our subjects, no well-defined differences in characteristics were observed between the alactatemia and hyperlactatemia groups ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical trials aimed at curbing the host inflammatory response to severe infection have yielded limited clinical success [3]. The mainstay of therapy for sepsis and septic shock remains 2-fold: (1) rapid treatment of the underlying infection and (2) early resuscitation to blunt physiologic abnormalities that potentiate disease progression [4]. The nature of these beneficial interventions focuses attention on rigorously defining the inciting insult caused by the pathogen.…”
Section: Inflammation: An Early S Aureus Insult In Sepsismentioning
confidence: 99%